REFLEKSI SISTEM DISTRIBUSI SYARIAH PADA LEMBAGA ZAKAT DAN WAKAF DALAM PEREKONOMIAN INDONESIA - Yuke Rahmawati (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2011)
The distribution activities always refer to subsistence and walfare. It is also closely linked to the issue of income distribution system. If there is an imbalance of income distribution, it will create an imbalance of wealth distribution. Therefore, There are two thingsthat must be followed in order to improve the well-being. They are reducing disparities among social groups with jobs and/or provide direct assistance to poor communities so they can improve their quality of life.DOI: 10.15408/aiq.v3i1.2498